Air–water flow characteristics in high-velocity free-surface flows with 50% void fraction. (October 2016) - Felder, Stefan; Chanson, Hubert
Highlights: Unique characterization of flow region with 50% void fraction in high-velocity free-surface flows. For 50% void fraction, largest bubble count rate, correlation time scales and turbulence levels. Analyses of instantaneous void fraction identified characteristic times scales. Chord times of about 3–5 ms characteristic time scale of flow region with equal air and water entities. Air–water interfaces in flow region with 50% void fraction affected by free-surface motions. Abstract: High-velocity free-surface flows are complex two-phase flows and limited information is available about the interactions between air and water for void fractions of about 50%. Herein a detailed experimental study was conducted in the intermediate flow region ( C ∼ 50%) on a stepped spillway and the microscopic air–water flow characteristics were investigated. The results showed differences in water and droplet chord times with comparatively larger number of air chord times (0–2 ms), and larger number of water chord times (2–6 ms). A monotonic decrease of particle chord modes was observed with increasing bubble count rates. Several characteristic time scales were identified based upon inter-particle arrival time analyses of characteristic chord time classes as well as spectral analyses of the instantaneous void fraction signal. Chord times of 3–5 ms appeared to be characteristic time scales of the intermediate flow region having similar time scales compared to the local correlation and integral turbulent time scales and to time scales associated with bubble break-up and turbulent velocity fluctuations. A further characteristic time scale of 100 ms was identified in a frequency analysis of instantaneous void fraction. This time scale was of the same order of magnitude as free-surface auto-correlation time scales suggesting that the air–water flow structure was affected by the free-surface fluctuations.